Association Between Intergenerational Support, Social Integration, and Subjective Well-Being Among Migrant Elderly Following Children in Jinan, China - Jia, Qingchen; Li, Shixue; Kong, Fanlei (Frontiers in Public Health, 2022)
Background: In China, as domestic urbanization progresses and immigration expands, an increasing number of older people are choosing to follow their migrant children to new cities; such people are referred to as “migrant elderly following children.” However, few studies have explored the subjective well-being of these older adults. The present study aims to investigate the factors that influence the subjective well-being of this population of older adults. Methods: This cross-sectional study was conducted on 656 older migrants who had followed their children to Jinan, Shandong Province, China. Multistage cluster random sampling was used. Binary logistic regression analyses were performed to explore, for this population, the relationships among intergenerational support, social integration, and subjective well-being. Results: Overall, 96.3% of the older migrants showed good subjective well-being. Analysis of intergenerational support showed that those who had a female child (odds ratio [OR] = 0.401, 95% confidence interval [95%CI]: 0.180, 0.893) and those whose children had terrible conjugal relationships (OR = 0.223, 95% CI: 0.099, 0.504) were less likely to have better subjective well-being. Analysis of social integration showed that migrants who liked their current city (OR = 5.358, 95%CI: 1.631, 17.599) and those who had a basic understanding of the local dialect (OR = 2.869, 95%CI: 1.203, 6.843) were more likely to have good subjective well-being. Migrants who had been hospitalized in the past year (OR = 0.216, 95%CI: 0.094, 0.497) were more likely to have poor subjective well-being. Conclusion: Intergenerational support and social integration are positively associated with the subjective well-being of migrant elderly following children in China. Efforts should be made, including the creation of specialized policies, to improve the family atmosphere of such migrants and their integration into their new cities, as this would contribute to improving their subjective well-being.